INNOVATIVE SUSTAINABLE STREETSCAPE DESIGN ALONG KEMBANG JEPUN CORRIDOR SURABAYA - Bambang Soemardiono; Murni Rachmawati; Defry Ardianta; Rahma Sakinah; Muhammad Syafiq; Arie Ranuari; Arina Marta Setya Putri; Deasy Tuffahati (Journal of Architecture&ENVIRONMENT, 2017)
Kembang Jepun is an area of the old city of Surabaya known under the name of the Lower Town or "Beneden Stad" that developed since the 18th century which has buildings with several different periods starting in the 1870s up to the 1900s. Now Kembang Jepun area has been known as dense area filled with commercial buildings and less paying attention to the condition of the streetscape. As a historic area that continues to operate actively, Kembang Jepun corridor has great streetscape potential to be developed to produce an attractive city situation in terms of environment, social conditions and supporting urban economic development. In fact there are problems for instance lacking in greenery and safety as well as historical atmosphere. For this purpose, the study will use a focus group discussion approach, which is a method of discussion with several stakeholders to provide innovative design ideas in the development of streetscape that has meaning in sustainable urban development, because stakeholder participation is an important key factor in the sustainable design process. The expected result of this research is to develop innovative streetscape designs in the corridor by develop the potentials and still maintaining the cultural heritage buildings.